Pendidikan Life Skills di Pesantren - Suharmoko Suharmoko (LPPM IAIN Sorong, 2018)
This study aims to know life skill implementation at Islamic Boarding School Darul Falah Be-Songo Ngaliyan Semarang. This study is a library research by examining various literature or relevant research as a source of data. The results of the study show that Islamic Boarding School Darul Falah Be-Songo Ngaliyan Semarang has organized activities that have life s skills. These skills include vocational skills and academic skills. Vocational skills here in the form of cooking skills, embroidery, make-up and other types of crafts. In addition, in it also taught how the students can speak well, both in expressing opinions and in speeches and other skills that become the main attraction for the surrounding community. The benefits, can improve the quality of thinking, quality of heart, and physical quality of students. In addition, for the environment in which the students are located or for the community can improve the life of advanced and civil. Furthermore, in the implementation carried out into three stages, namely the stage of planning, implementation phase, and evaluation phase that all done aimed for this Education in accordance with the suggestions have made